2022
DOI: 10.3390/ph16010022
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Efficacy of Extracts and Isolated Bioactive Compounds from Ascomycota Fungi in the Treatment of Colorectal Cancer: A Systematic Review

Abstract: Colorectal cancer (CRC) is the second leading cause of cancer-related deaths worldwide. Despite the advances and success of current treatments (e.g., chemotherapy), there are multiple serious side effects which require the development of new treatment strategies. In recent years, fungi have gained considerable attention as a source of extracts and bioactive compounds with antitumor capabilities because of their antimicrobial and antioxidant properties and even their anti-inflammatory and antiviral activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 94 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…Deng et al found significantly higher levels of YEATS4 in colorectal cancer tissues than in normal para-cancerous tissues; however, this did not affect the overall survival of patients. When YEATS4 is knocked down in colorectal cancer cells, the cells are arrested in the G0/G1 phase and cell growth is inhibited ( Tao et al, 2015 ; Luque et al, 2022 ). Subsequent studies have indicated that miR-218 can negatively regulate YEATS4 expression, thereby attenuating cellular resistance to L-OHP, impairing cellular autophagy protection, and inhibiting colorectal cancer progression ( Fu et al, 2016 ).…”
Section: Yeats4 and Human Cancermentioning
confidence: 99%
“…Deng et al found significantly higher levels of YEATS4 in colorectal cancer tissues than in normal para-cancerous tissues; however, this did not affect the overall survival of patients. When YEATS4 is knocked down in colorectal cancer cells, the cells are arrested in the G0/G1 phase and cell growth is inhibited ( Tao et al, 2015 ; Luque et al, 2022 ). Subsequent studies have indicated that miR-218 can negatively regulate YEATS4 expression, thereby attenuating cellular resistance to L-OHP, impairing cellular autophagy protection, and inhibiting colorectal cancer progression ( Fu et al, 2016 ).…”
Section: Yeats4 and Human Cancermentioning
confidence: 99%
“…In this context, marine microorganisms have been explored as a source of new therapeutic biomolecules that may be effective against CRC [10,11], the third most frequent tumor in the world, with an estimated increase in malignancy of 60% by 2030 [12]. Despite advances in the physiopathology of this tumor, which have determined the three precursor pathways for CRC lesions, chromosomal instability (70-90% of cases), serrated neoplasm (10-20% of cases) and microsatellite instability (2-7% of cases), there have been no significant advances in therapy in recent years.…”
Section: Introductionmentioning
confidence: 99%